Urbanization, Green Finance, and Environmental Sustainability in Pakistan - Farooq, Fatima; Shah, Said Zamin; Faheem, Muhammad; Nousheen, Asma (Pakistan Journal of Humanities and Social Sciences, 2024)
Sustainable development is a key objective of all countries in recent years. Therefore, accounting for the role of urbanization as essential parts of sustainable development, we have evaluated the impact of green finance, urbanization, GDP, and FD on CO2 emissions for Pakistan from 1983 to 2023. We applied the NARDL technique to examine the asymmetric correspondences between studied variables. The practical observations unveiled a conclusive association between CO2 emission and urbanization in positive shocks, while in negative shocks, urbanization purifies the environment. In terms of green finance and FD, the findings displayed a favorable impact of GF and FD on the environmental quality in Pakistan. GDP showed a positive relationship with CO2 as it enhances CO2 in the long term. In view of the findings, policymakers are suggested to advance rural areas, design planned cities, and encourage green finance to practice eco-friendly projects.